The Pathogenesis of COVID-19 Myocardial Injury: An Immunohistochemical Study of Postmortem Biopsies - Hartmann, Camila; Miggiolaro, Anna Flavia Ribeiro dos Santos; Motta, Jarbas da Silva; Baena Carstens, Lucas; Busatta Vaz De Paula, Caroline; Fagundes Grobe, Sarah; Hermann de Souza Nunes, Larissa; Lenci Marques, Gustavo; Libby, Peter; Zytynski Moura, Lidia; de Noronha, Lucia; Pellegrino Baena, Cristina (Frontiers in Immunology, 2021)
Rationale Myocardial injury associates significantly and independently with mortality in COVID-19 patients. However, the pathogenesis of myocardial injury in COVID-19 remains unclear, and cardiac involvement by SARS-CoV-2 presents a major challenge worldwide. Objective This histological and immunohistochemical study sought to clarify the pathogenesis and propose a mechanism with pathways involved in COVID-19 myocardial injury. Methods and Results Postmortem minimally invasive autopsies were performed in six patients who died from COVID-19, and the myocardium samples were compared to a control group (n=11). Histological analysis was performed using hematoxylin-eosin and toluidine blue staining. Immunohistochemical (IHC) staining was performed using monoclonal antibodies against targets: caspase-1, caspase-9, gasdermin-d, ICAM-1, IL-1β, IL-4, IL-6, CD163, TNF-α, TGF-β, MMP-9, type 1 and type 3 collagen. The samples were also assessed for apoptotic cells by TUNEL. Histological analysis showed severe pericardiocyte interstitial edema and higher mast cells counts per high-power field in all COVID-19 myocardium samples. The IHC analysis showed increased expression of caspase-1, ICAM-1, IL-1β, IL-6, MMP-9, TNF-α, and other markers in the hearts of COVID-19 patients. Expression of caspase-9 did not differ from the controls, while gasdermin-d expression was less. The TUNEL assay was positive in all the COVID-19 samples supporting endothelial apoptosis. Conclusions The pathogenesis of COVID-19 myocardial injury does not seem to relate to primary myocardiocyte involvement but to local inflammation with associated interstitial edema. We found heightened TGF-β and interstitial collagen expression in COVID-affected hearts, a potential harbinger of chronic myocardial fibrosis. These results suggest a need for continued clinical surveillance of patients for myocardial dysfunction and arrythmias after recovery from the acute phase of COVID-19.